Network Pharmacology-Based Dissection of the Anti-diabetic Mechanism of Lobelia chinensis - Ge, Qi; Chen, Liang; Yuan, Yi; Liu, Lanlan; Feng, Fan; Lv, Peng; Ma, Shangshang; Chen, Keping; Yao, Qin (Frontiers in Pharmacology, 2020)
Diabetes mellitus (DM) is a chronic inflammatory disease, and the rapidly increasing DM is becoming a major problem of global public health. Traditional Chinese medicine (TCM) has a long history of treating diabetes. It has been developed and utilized because of its good efficacy and no toxic side effects. Lobeliae chinensis is a traditional whole grass herbal. With the continuous deepening of pharmacological research on TCM, the active ingredients of Lobeliae chinensis are continuously revealed, which contained the alkaloids, flavonoids, flavonoid glycosides and amino acids that have the good effects of anti-inflammatory, anti-viral and anti-diabetic. In order to further explore the targets of active ingredients and its anti-diabetic mechanism, a feasible network pharmacology analysis model based on chemical, pharmacokinetic and pharmacological data was developed by network construction method to clarify the anti-diabetic mechanism of Lobeliae chinensis. The present study conducted by gas chromatography-mass spectrometer (GC/MS), which identified 208 metabolites of Lobeliae chinensis, of which 23 ingredients may have effective pharmacological effects after ADME screening. Network pharmacological analysis on the active ingredients revealed that 5-Hydroxymethylfurfural in Lobeliae chinensis affects the insulin resistance signaling pathway by acting on GSK3B, TNF, and MAPK1, acacetin affects the diabetic pathway by acting on INSR, DPP4, GSK3B, that regulate type 2 diabetes, non-insulin-dependent diabetes mellitus and inflammatory diseases. These results successfully indicated the potential anti-diabetic mechanism of the active ingredients of Lobeliae chinensis.